Antibiotic-Resistant Enterococci in Seawater and Sediments from a Coastal Fish Farm - Di Cesare, Andrea; Vignaroli, Carla; Luna, Gian Marco; Pasquaroli, Sonia; Biavasco, Francesca (Microbial drug resistance (Larchmont, N.Y.), 2012)
The aim of this study was to detect and characterize antibiotic-resistant enterococci in seawater and sediment from a Mediterranean aquaculture site where no antibiotics are used. Colonies (650) grown on Slanetz-Bartley (SB) agar were amplified on antibiotic-supplemented SB, and erythromycin (ERY), tetracycline (TET), and ampicillin (AMP) MICs were determined. Of 75 resistant isolates (17 to TET, 5 to ERY, and 45 to AMP), 5 Enterococcus faecalis , 25 E. faecium , 5 E. casseliflavus , 1 E. gallinarum , 1 E. durans , and 23 Enterococcus spp. were identified by genus- and species-specific polymerase chain reaction (PCR). tet (M), tet (O), tet (L), tet (K), erm (B), erm (A), erm (C), mef , msr , blaZ , and int (Tn 916 ) were sought by PCR, including an improved multiplex PCR assay targeting tet (M), tet (L), and erm (B). Tet (M) was the most frequent TET resistance gene; msr (C) was the sole ERY resistance gene detected. blaZ was found in 29/45 AMP-resistant isolates; however, no β-lactamase production was detected. Antibiotic-resistant enterococci were recovered 2 km off the coast despite the absence of selective pressure exerted by antibiotic use. The occurrence of resistant strains in the absence of the tested genes may indicate the presence of less common resistance determinants. This first evidence of resistant enterococci at a Mediterranean aquaculture site suggests the existence of a marine reservoir of antibiotic resistances potentially transmissible to virulent strains that could be affected by mariculture in an antibiotic-independent manner.